Hannibal : Rome's greatest enemy - Hoyos, B. D. (B. Dexter), 1944- (Greece and Rome live., 2008)
From the Publisher: Hannibal's enduring reputation as a man and as a general is due to his enemies' fascination with him. The way his legend was shaped in the Greek and Roman consciousness is one of the book's main themes. Under Hannibal's leadership, Carthage came close to dominating the western Mediterranean; his total victory would have changed the course of history. That he was a brilliant general is unquestioned, and his strategy and tactics have been studied as real-life lessons in war, even into the modern era. His political career is less appreciated and his achievements as civilian leader of Carthage in 196-5 BC have been virtually overlooked. The issue of whether he might indeed have changed history had he postponed conflict with Rome and concentrated first on Carthage's own prosperity and safety is explored in this volume as vigorously as the military questions.